Right to Travel and National Security - William B. Gould (Washington University Law Quarterly, 1961)
The right to travel has been deeply enmeshed in the Anglo-American tradition. In the relatively small country of England this need was particularly obvious, and there can be little doubt that both England and the United States owe a great deal of their commercial and intellectual growth to the freedom of international mobility.
Keywords: Civil rights; Constitutional law – United States; Passports